Maîtriser le temps ? - Benoit Bastard; David Delvaux; Christian Mouhanna; Frédéric Schoenaers (Temporalités)
This article broaches the question of time in the Judiciary by studying family litigations. Taking the time dimension into account when settling the conflicts that emerge during a divorce, it points to the radical change that has intervened in the vision of time over the past decades, affecting the world of civil justice. The acceleration of the judiciary institution as a whole has increased two-fold in this domain due to the urgency created by massive litigation: family conflicts must be dealt with rapidly in ways adapted to the interested parties’ needs. The study is based on a survey carried out in five jurisdictions in France and Belgium. In both countries, the most recent reforms have aimed at speeding up divorce procedures. In actual practice, one notes various ways of doing so. In France, as the central actor who deals with all the sorts of separation that concern the courts, the family judge does all he/she can to speed up a decision, by leaning as much as possible on mutual consent and trying to control the lawyers. In Belgium, the acceleration is particularly visible in divorce cases but decisions concerning the side effects of the separation are sent on to various instances which all observe their own temporality. Beyond these differences, the comparison suggests that accelerating the treatment of family conflicts is the result of two major trends: the managerialization of Justice and sending decisions relative to the family back to the interested parties themselves. Accelerating the legal treatment of divorce is however not devoid of consequences: in particular, it radically underscores the difference between the time a trial takes and the time the estranged couples must live through.